2020
DOI: 10.5999/aps.2020.00220
|View full text |Cite
|
Sign up to set email alerts
|

Modified everting sutures combined with reattachment to the inferior tarsal plate for involutional lower eyelid entropion: A new technique

Abstract: Background This study evaluated the outcomes of a new modified Wies technique for patients with involutional lower eyelid entropion without horizontal eyelid laxity.Methods This case series retrospectively analyzed consecutive patients with entropion who underwent surgery between January 2014 and March 2019 by the same experienced surgeon. Horizontal eyelid laxity, lower eyelid retractor function, and orbicularis muscle overriding were recorded before and after surgery. The recurrence rate and complications we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…7,9,17,19,[23][24][25][26] Another type of technique to correct LEIE is blind retractor plication using everting sutures of the lower eyelid (Quickert or Wies sutures). [32][33][34] Consistent with other studies, the success rates for the ARR and PRR approaches were similar. 7,15,17,22,[24][25][26] However, PRR is faster and easier to perform because retractors can be found just behind the conjunctiva, no skin incisions are required, the orbicularis muscle and the possibility of bleeding are avoided and there is no visible scar.…”
Section: Discussionsupporting
confidence: 88%
“…7,9,17,19,[23][24][25][26] Another type of technique to correct LEIE is blind retractor plication using everting sutures of the lower eyelid (Quickert or Wies sutures). [32][33][34] Consistent with other studies, the success rates for the ARR and PRR approaches were similar. 7,15,17,22,[24][25][26] However, PRR is faster and easier to perform because retractors can be found just behind the conjunctiva, no skin incisions are required, the orbicularis muscle and the possibility of bleeding are avoided and there is no visible scar.…”
Section: Discussionsupporting
confidence: 88%
“…An ES technique is an affordable and straightforward method of entropion correction which can be performed rapidly, often upon the patient's first visit to the hospital. [ 24 25 26 ] The sutures help to plicate the attenuated inferior eyelid retractors and transfer their pull to the anterior surface of the lower tarsus. They also create a horizontal barrier to prevent the preseptal orbicularis oculi muscle migration.…”
Section: Discussionmentioning
confidence: 99%
“…Sen and Yalcinsoy reported a success rate of 96.4% over a mean follow-up period of 27 months using an incision-based modified ES technique, while Han et al reported an overall success rate of 93.5% after mini-incisional entropion repair involving sutures. [ 26 , 30 ] A study by Rougraff et al demonstrated a success rate of 78% using fornix sutures and LTS with a minimum of 18 months’ follow-up. [ 31 ]…”
Section: Discussionmentioning
confidence: 99%
“…18 An ES technique is an affordable and simple method of entropion correction which can be performed rapidly, often upon the patient's first visit to hospital. [22][23][24] The sutures help to plicate the attenuated inferior eyelid retractors and transfer their pull to the anterior surface of the lower tarsus; in addition, they also create a horizontal barrier to prevent the migration of the preseptal orbicularis oculi muscle. The successful outcome of this procedure depends on forming a fibrotic scar along the suture tracks.…”
Section: Discussionmentioning
confidence: 99%
“…reported an overall success rate of 93.5% after mini-incisional entropion repair involving sutures. 24,30 A study by Rougraff et al demonstrated a success rate of 78% using fornix sutures and LTS with a minimum of 18 months follow-up. 31 Unfortunately, the ES technique alone offers only temporary correction of the involutional entropion.…”
Section: Discussionmentioning
confidence: 99%